Assessing the Burden of Laboratory-Confirmed Respiratory Syncytial Virus Infection in a Population Cohort of Australian Children Through Record Linkage. (7th February 2020) - Moore, Hannah C; Lim, Faye J; Fathima, Parveen; Barnes, Rosanne; Smith, David W; de Klerk, Nicholas; Blyth, Christopher C
Abstract: Background: Significant progress has been made towards an effective respiratory syncytial virus (RSV) vaccine. Age-stratified estimates of RSV burden are urgently needed for vaccine implementation. Current estimates are limited to small cohorts or clinical coding data only. We present estimates of laboratory-confirmed RSV across multiple severity levels. Methods: We linked laboratory, perinatal, and hospital data of 469 589 children born in Western Australia in 1996–2012. Respiratory syncytial virus tests and detections were classified into community, emergency department (ED), and hospital levels to estimate infection rates. Clinical diagnoses given to children with RSV infection presenting to ED or hospitalized were identified. Results: In 2000–2012, 10% (n = 45 699) of children were tested for RSV and 16% (n = 11 461) of these tested positive. Respiratory syncytial virus was detected in community, ED (both 0.3 per 1000 child-years), and hospital (2.4 per 1000 child-years) settings. Respiratory syncytial virus-confirmed rates were highest among children aged <3 months (31 per 1000 child-years). At least one third of children with RSV infection presenting to ED were diagnosed as other infection, other respiratory, or other (eg, agranulocytosis). Conclusions: Respiratory syncytial virus is pervasive across multiple severity levels and diagnoses. Vaccines targeting children <3 months must be prioritized. Given that most children are never tested, estimating the under-ascertainment of RSV infection is imperative. Abstract : We report the first population-based, laboratory-confirmed, age-stratified RSV infection rates in Australian children under 16 years. RSV was detected across community, emergency department, and in-hospital settings. Children positive for RSV received a range of diagnoses, including nonrespiratory diagnoses (eg, agranulocytosis).